2013
DOI: 10.1039/c3dt33079f
|View full text |Cite
|
Sign up to set email alerts
|

Long phosphorescent Ca2SnO4 with minuscule rare earth dopant concentration

Abstract: Rare-earth doped Ca2SnO4 phosphors were synthesized using a conventional solid state reaction method. The red phosphorescence of Eu(3+) was observed in this system with persistence time. In the as-prepared samples, the doped rare earth ions occupied both Ca and Sn sites in the host lattice. The longest phosphorescent persistence property can be achieved for the Ca2SnO4 phosphors with a 0.1% Eu dopant. Depending on the doped rare earth ions, afterglow emissions of various colors were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Persistent luminescence is a phenomenon whereby luminescence can last for hours (or even more, recently reported upto few days) aer the stoppage of the excitation. [44][45][46][47][48][49][50][51][52][53] As mentioned earlier, it is generally accepted that, the presence of lattice defects causes the evolution of trap levels, which play a central role for the aerglow/persistent luminescence in some potentially efficient luminescent materials. However, even aer a long history of work on persistent luminescence, the fundamental of each and every step involved in this phenomenon is still not unanimously accepted, and more than one explanations are available in published articles to explain certain processes.…”
Section: Persistent Luminescencementioning
confidence: 99%
See 1 more Smart Citation
“…Persistent luminescence is a phenomenon whereby luminescence can last for hours (or even more, recently reported upto few days) aer the stoppage of the excitation. [44][45][46][47][48][49][50][51][52][53] As mentioned earlier, it is generally accepted that, the presence of lattice defects causes the evolution of trap levels, which play a central role for the aerglow/persistent luminescence in some potentially efficient luminescent materials. However, even aer a long history of work on persistent luminescence, the fundamental of each and every step involved in this phenomenon is still not unanimously accepted, and more than one explanations are available in published articles to explain certain processes.…”
Section: Persistent Luminescencementioning
confidence: 99%
“…Recently, Tadashi et al explored the persistent luminescence of most of the lanthanide ions in a Ca 2 SnO 4 host. 45 Fig. 3 shows a beautiful digital image of both the emission and aerglow by different lanthanide ions.…”
Section: Persistent Luminescencementioning
confidence: 99%
“…26 In addition, we can easily distinguish the characteristic lines located at 362, 383, 395, 417, and 466 nm corresponding to the transitions of Eu 3+ ions from the ground level 7 F 0 to the 5 D 4 , 5 L 7 , 5 L 6 , 5 D 3 , and 5 D 2 excited levels, respectively. 39 The PL spectrum of the LGW:5% Eu 3+ phosphor is obtained by exciting at 275 nm. It can be found that the strongest emission peak of LGW:5% Eu 3+ is located at 617 nm, which originates from the 5 D 0 / 7 F 2 transition of Eu 3+ .…”
Section: Photoluminescence Propertiesmentioning
confidence: 99%
“…11 In particular, CaSnO 3 is of great interest due to its phenomenal optical properties, excellent resistance to chemical vulnerabilities, and high mechanical strength. 12,13 Apart from this, CaSnO 3 also possess some special inherent properties that readily substantiates its suitability as a host matrix for designing a good phosphor material.…”
Section: Introductionmentioning
confidence: 99%